Toward an understanding of student Erasmus+ traineeships of Prague University of Economics and Business - Eva Grebe (World Economy and Policy (WEP), 2022)
The author aims to provide a basic analysis in the form of a comprehensive overview, map indicators, motivational factors, and benefits of traineeships of the Prague University of Economics and Business (hereafter referred to as VéSE) students who completed traineeships in 2014-2019 and were financially supported by the Erasmus+ programme. Among the student's obligations to provide this financial support is their final report from the mobility, completed in the Mobility Tool of the European Commission. As the author has access to this database and the final reports as part of her work at VéSE, it is this database of completed questionnaires that provides an overview of students' motivation for traineeships abroad and their contribution in terms of personal and professional.
Keywords: 330; mobility; tertiary education; traineeship; Erasmus; motivation; skill